Comparison of Insulin Expression Levels in White Blood Cells of infants with and without Family History of Type II Diabetes - Mazhari, Reza; Mirfakhraie, Reza; Asadi, Mojgan; Alipour Olyaei, Nasrin; Kheiri, Hamidreza; Moslemi, Elham; Khanmohamadi, Mahnaz; Tohidnejad, Elham; Yasaee, Vahid Reza (Novelty in Biomedicine, 2016)
Background: Type II diabetes is known as one of the most important, prevalent, and expensive diseases of mankind. Late diagnosis and subsequent delayed initiation of treatment or surveillance of patients create a variety of problems for affected individuals. This has raised increasing concerns for public health authorities throughout the world. In the current study, we aimed to find a new approach for early identification of high-risk individuals at initial months of their life. This allows us to take preventive measures as early as possible. Materials and Methods: In our study, 102 infants - from one to six months - were selected and placed in two case and control groups. The case group contained 52 babies with at least one of their parents identified as a type II diabetic patient. The control group comprised 50 babies with no family history of type II diabetes in paternal and maternal first-degree relatives. Afterwards, the expression level of insulin gene was analyzed in white blood cells of both groups. Information related to infants - referred to outpatient and inpatient wards of three main pediatric hospitals placed in Tehran - and their parents were collected through questionnaires within a two-year period. The study inclusion criteria for infants were confirmed type II diabetes in at least one of their parents, the absence of any metabolic disorder, and the absence of any disturbing vital signs. After drawing 2 ml of babies’ peripheral blood, total RNA of white blood cells (WBC) was extracted, and used for cDNA synthesis. Real-Time PCR was then applied to quantitatively evaluate the expression levels of insulin gene. The results of Real-Time PCR were statistically analyzed by non-parametric tests of Mann-Whitney and Kruskal-Wallis. Results: The expression of insulin gene was observed in white blood cells of all samples. However, there was a significant difference in expression levels between case and control groups (p<0.05). There was a statistically significant difference in mean levels of gene expression among babies with diabetic mother, and healthy groups (RQ=0.5, P-value=0.002), but this value wasn’t significant for babies with diabetic father (RQ=0.78, P>0.05). Conclusion: Numerous genes contribute to the development of diabetes and novel disease-causing genes are increasingly being discovered. Identification of disease-prone individuals through examining merely one underlying gene is complicated and challenging. Interestingly, all of these abnormally functioning genes finally manifest themselves in the altered expression levels of insulin gene. The expression status of insulin gene in WBCs could be suggested as a useful approach for identification of individuals at high risk for developing diabetes. This paves the way for taking appropriate measures at infancy period in order to prevent the disease as well as inhibit its various side effects in the following years of patient’s life.